2009
DOI: 10.1042/bj20080805
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of energy-producing pathways of HepG2 cells by 3-bromopyruvate1

Abstract: 3-BrPA (3-bromopyruvate) is an alkylating agent with anti-tumoral activity on hepatocellular carcinoma. This compound inhibits cellular ATP production owing to its action on glycolysis and oxidative phosphorylation; however, the specific metabolic steps and mechanisms of 3-BrPA action in human hepatocellular carcinomas, particularly its effects on mitochondrial energetics, are poorly understood. In the present study it was found that incubation of HepG2 cells with a low concentration of 3-BrPA for a short peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
124
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(132 citation statements)
references
References 46 publications
7
124
0
1
Order By: Relevance
“…HK is also a target of 3--bromopyruvate, a compound shown to be toxic to cancer cells 91,95 . However, 3--bromopyruvate is also toxic to some cancer cells at concentrations that are too low to inhibit HK and it has been argued that the combined inhibition of multiple metabolic enzymes accounts for the toxic effects of this compound on cancer cells 96 .…”
Section: --Deoxyglucose (2dg) Is An Inhibitor Of Glucose Metabolism mentioning
confidence: 99%
“…HK is also a target of 3--bromopyruvate, a compound shown to be toxic to cancer cells 91,95 . However, 3--bromopyruvate is also toxic to some cancer cells at concentrations that are too low to inhibit HK and it has been argued that the combined inhibition of multiple metabolic enzymes accounts for the toxic effects of this compound on cancer cells 96 .…”
Section: --Deoxyglucose (2dg) Is An Inhibitor Of Glucose Metabolism mentioning
confidence: 99%
“…Therefore, therapeutic strategies should focus on both targets, glycolysis and mitochondrial OXPHOS. Even though some studies reported that mitochondrial OXPHOS is also one of 3-BP targets [185] , 3-BP has been mainly demonstrated to be the most potent glycolytic inhibitor among various types of inhibitors. However, including our studies, the results of in vivo studies that have used human HCC cell lines did not exhibit complete remission, but showed only partial remission after 3-BP treatment [18,19, .…”
Section: Therapeutic Implications Of Targeting the Metabolic Interactmentioning
confidence: 99%
“…3-Bromopyruvate (3-BrPA) is a halogenated and alkylating analog of pyruvic acid able to curb the growth of many tumors, frequently refractory to standard therapeutics, by compromising ATP synthesis through the inhibition of glycolysis and mitochondrial complex II activity (12)(13)(14)(15)(16). In accordance with current challenges aimed at identifying metabolic conditions chemopotentiating the effectiveness of antitumor drugs, our study argues for the ability of glutamine deprivation to sensitize carcinoma cells to the cytotoxic effects of 3-BrPA both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%